The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/tbj.12045
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Adherence in a Chemoprevention Trial among Women at Increased Risk for Breast Cancer Attending the Modena Familial Breast and Ovarian Cancer Center (Italy)

Abstract: Chemoprevention for women at risk for breast cancer has been shown to be effective, but in actual practice, women's uptake of chemoprevention has been poor. We explored factors that influence acceptability, adherence, and dropout in the International Breast (Prevention) Intervention Study during our first 3 years of activity at the Modena Familial Breast and Ovarian Cancer Center. We evaluated socio-demographic characteristics, health status, adherence, and side effect intensity. Semi-structured interviews ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…9 However, the design of these studies was subject to bias because of retrospective recall when completing the off-therapy forms and an inability to compare adherence rates between those who did and did not experience adverse effects. 20-23 Data from the NSABP P-1 trial has demonstrated the role of gynecologic, vasomotor, and sexual symptoms on adherence at 1-year follow-up. 17 Our analysis adds to these data by demonstrating that more than one fifth of 5-year nonadherence can be explained by participant-reported early symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 However, the design of these studies was subject to bias because of retrospective recall when completing the off-therapy forms and an inability to compare adherence rates between those who did and did not experience adverse effects. 20-23 Data from the NSABP P-1 trial has demonstrated the role of gynecologic, vasomotor, and sexual symptoms on adherence at 1-year follow-up. 17 Our analysis adds to these data by demonstrating that more than one fifth of 5-year nonadherence can be explained by participant-reported early symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…9 Studies that collected off-therapy forms report that more than half of all women who drop out of preventive therapy trials attribute their decision to adverse effects of medication. 20-23 However, retrospectively assessing decisions to discontinue medications may be a biased approach.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, intermittent therapy with PARP inhibitors could be a viable approach for chemoprevention and its potential benefits, if translated into clinical practice, could be marked for high-risk patients with BRCA1 mutations. Moreover, intermittent dosing could also potentially circumvent one of the major challenges in chemoprevention regimens, namely poor adherence because of cost, unfavorable side effects and the duration of drug exposure (61, 62). …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, an accurate risk assessment in these high-risk populations remains fundamental, in order to establish personalized strategies for risk control (i.e. surveillance, chemoprevention [15] and prophylactic surgery [16]). At this aim, reproductive factors were investigated in a population of Italian women attending the Modena Family Cancer Clinic (MFCC), comparing women classified at different levels of increased BC risk.…”
Section: Introductionmentioning
confidence: 99%